Regenerative Medicine and cell Therapy - Stoltz, Jean-François (IOS Press, 2014)
This book does not claim to be a handbook which covers all aspects of regenerative medicine or cell therapy. For those purposes, a much larger volume would be needed. In this volume, the first part (11 chapters), is devoted to basic knowledge of stem cells. The second part (20 chapters) is dedicated to potential clinical applications (hematology, cardiac, vascular, osteoarticular, liver, skin, etc.) without having been able to envisage all the applications that will doubtless be developed in the coming decade. We hope that this book will provide a stimulus for basic researchers and clinicians involved in regenerative medicine or cell therapy.